Insights into brand authenticity and customer engagement in a restaurant setting: A text mining approach - Rosado-Pinto, F.; Loureiro, S. M. C.; Bilro, R.G. (Proceedings of the 48th EMAC Conference, 2019)
The aim of this study is to analyze the dimensions of customer engagement, brand authenticity and other related constructs (need for uniqueness and brand love) in customers’ online reviews through text-mining and sentiment analysis trends. This study focuses on Yelp.com comments and use a random sample of 3,877 reviews of restaurants, in ten cities in the USA. A customer engagement and authenticity dictionaries are created, based on previously validated scales and extended using WordNet 2.1. Findings reveal that cognitive processing is the strongest dimension of consumer engagement. Results further indicate that brand love presents lower polarity value compared to brand authenticity, which means that consumer tend to value more the perception of authenticity than the love relationship with the brand to become more engaged.